2021
DOI: 10.1177/00405175211051949
|View full text |Cite
|
Sign up to set email alerts
|

A review of textile-based electrodes developed for electrostimulation

Abstract: Electrical stimulation can be used for the treatment of various nerve and muscle injuries as well as acute and chronic pain conditions. An electrical pulse is applied to a muscle or nerve to activate excitable tissue using internal or external electrodes with the aim of building muscle strength, artificially creating or supporting limb movement or reducing pain. Textile electrodes offer several advantages over conventionally used disposable surface electrodes: they are flexible and re-usable and they do not re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 102 publications
0
14
0
Order By: Relevance
“…129 From the sustainability perspective, the recycling the Micro/Nano electromechanical systems (MEMS/NEMS) incorporated in to the fabric is challenging and is under review. 130,131 Dry textile electrodes sometimes perform less than the gel electrodes especially, when motion artifact are present. Researchers have suggested applying sufficient quantity of water or saline solution onto the dry electrodes to achieve performance comparable to that of the conventional gel electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…129 From the sustainability perspective, the recycling the Micro/Nano electromechanical systems (MEMS/NEMS) incorporated in to the fabric is challenging and is under review. 130,131 Dry textile electrodes sometimes perform less than the gel electrodes especially, when motion artifact are present. Researchers have suggested applying sufficient quantity of water or saline solution onto the dry electrodes to achieve performance comparable to that of the conventional gel electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of textile electrodes for stimulation Euler et al has mapped out much of the work done hitherto. They found that the samples investigated ranged over most common textile techniques: printing, coating, knitting, weaving and non-woven methods 20 . In a related paper by the same group, they found that a high density of yarns if favourable, and that in the case of dry electrodes that an uneven surface is beneficial 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Textile-based electrodes, a type of dry electrode, are being developed by fabricating fabrics, such as knitting, weaving, and embroidery, using metal wire or conductive yarn, or coating or printing on various substrate materials [15][16][17][18][19]. In this case, the inner electrode of the clothing must be in contact with the skin to collect bio-signals, and the outer electrode must be designed to connect to a device capable of collecting electromyography.…”
Section: Introductionmentioning
confidence: 99%